Cross-Border Patent Disputes: Unified Patent Court or International Commercial Arbitration? - Alba Betancourt, Ana (Utrecht Journal of International and European Law, 2016)
Currently, the enforcement of a patent that is registered in several countries involves the risk of getting different and conflicting decisions from the national courts. In 2013, 25 European countries entered in an agreement that aims to homogenise the patent system by creating the European patent with unitary effect and a Unified Patent Court (UPC). This article focuses on the UPC, which aims to have a single court proceeding for cross-border patent conflicts. Does the UPC system represent an advantage compared to the current litigation system? The paper argues that it does and explores what it considers to be the two main advantages of a UPC over the current system of cross-border litigation of patents: the ability to drag several conflicts to a single procedure and the neutrality of the decision makers. These advantages are consequently compared to the characteristics of arbitration. Then, an explanation is provided with regards to how the UPC system is going to work in terms of jurisdiction, preliminary injunctions, the choice of law and enforcement of decisions, comparing those same procedural aspects to arbitration. The article finds that arbitration involves many of the same advantages (as compared to the UPC) and that the procedural issues studied in both means are, so too, similar. Therefore, arbitration represents a viable alternative to the UPC when it comes to reducing the risks in solving cross-border patent conflicts.